Comparative study of knowledge and practices regarding tuberculosis amongst the nursing staff of medical college and peripheral health care unit - Gupta, Rajat; Sood, Anuradha; Kaistha, Madhvi; Bhardwaj, Ashok; Sharma, Tarun (International Journal Of Community Medicine And Public Health, 2017)
Background: One of the major risk factor for tuberculosis (TB) includes working in close proximity to the patients. Recent evidence suggests that nursing professionals are vulnerable to tuberculosis not only because of elevated exposure, but also because of misinformation and lack of updated data regarding knowledge about the disease. Our study aimed to gather knowledge and health care practices related to TB amongst nurses in a medical college and that of a peripheral health care unit. The objectives of the study were to compare the level of knowledge regarding tuberculosis and practices related to it in nursing staff of a Medical College and nursing staff working at peripheral health care unit. Methods: This cross-sectional study was conducted in a rural medical college and a training centre for health professionals of Himachal Pradesh over a period of 3 months (w.e.f. October–December, 2014). A total of randomly selected staff nurses of medical college and nurses working at different levels of peripheral health care unit attending training at the Training Centre, Chheb Kangra were included in the study. A structured questionnaire was framed to collect data regarding tuberculosis and its practices. Results: It was observed that nursing staff posted in Medical College had less knowledge as compared to the nursing staff of a peripheral health care unit. Amongst the nursing staff of the periphery the best knowledge was observed in staff posted at Community Health Centre and lowest in staff posted at PHC. In Medical College to our surprise nursing staff of surgery and obstetrics and gynae had superior knowledge as compared to Medicine ward. Conclusions: Training under RNTCP should be targeted not only towards nurses working in peripheral health units but also in nurses working in medical colleges.